Comparison of ideologies, discursive strategies and power in the tweets of two political leaders in Asia - Ramanathan, Renugah (2017)
It is worth noting that much discourse studies have been conducted on political discourse in social media focusing on politician’s activities, leadership skills and active participation on Twitter. However, little research has been done on discourse of political leaders in Asia on their power in use and identity. In relation to this, it could be said that discourse of political leaders in Asia has got various cultural and political significance because of its authenticity role in shaping the life of the Asian communities. The scarcity of research on Asian politicians and microblog has prompted the researcher to highlight the ideologies and discursive strategies in the discourse of Prime Minister Najib Tun Razak (henceforth, Najib) from Malaysia and Prime Minister Narendra Modi (henceforth, Modi) from India on Twitter during the national elections. The universality of the Asian leaders stem from their influential ideologies and discursive strategies that have effected their discourse and the citizens. This study aims to conduct a critical discourse analysis to investigate the various political ideologies and discursive strategies that are presented in the tweets of Najib and Modi during national elections and a comparison of power and identity between Najib and Modi is done to perceive the collective experience between the politicians and citizens in building a unified nation. For this purpose, Najib and Modi election tweets were chosen to be analysed in this study. The objective of choosing the election tweets is due to a higher content of ideologies that is disseminated to the citizens. The emerging topics were discovered through Yule and Brown (1983) topic framework. To uncover the embedded ideologies in the tweets Van Dijk’s (2004) Categories of Ideological Analysis were utilized in this study. Besides, metaphors and speech acts were identified through Group (2007) Metaphor Identification Procedure and Searle (1979) speech act categories. Furthermore, metaphors and speech acts were semantically categories into Wodak’s (2005) Discursive Strategies for Positive Self-Presentation and Negative Other-Presentation. The findings of the analysis showed that the utilization of Van Dijk’s ideological categories; positive self-presentation, negative other-presentation and national glorification were closely related to the ideologies embedded. The ideologies such as democracy, unity, technological elections and economic were explored and discussed. The ideological analysis also manifested that Najib and Modi have formed their own social identities during the national elections through the employment of certain linguistic forms such as the usage of Us which emphasizes on the in-groups and Them to portray the out-group. With the help of Van Dijk’s ideological categories, topics that emerged throughout the elections campaigns in Malaysia and India were spotted; international recognition, employability, social-economics and leadership of women. Wodak’s (2005) discursive strategies were utilized to perceive social, political and physiological aspects during the national elections. Searle’s speech acts; commissives and directives were collaborated with Wodak’s discursive strategies to strengthen the intended meaning of the tweets and to provide citizens with information on different social, politics and cultural issues. Besides, the usage of metaphors are found in the tweets of both the political leaders which presented the way language is used figuratively to describe the citizens and the politicians. The metaphors which were spotted were in relation to concept of nation building; Election is Building and Election is a Journey which depicts the theme of nation construction. Through the discourse of Najib and Modi, it can be perceived that consensual power is employed by Najib and Modi throughout the national elections. This is because the citizens accept the ideologies disseminated via discourse thus making the elections a success. The differences between the discourse of Najib and Modi is observed through the identity of nationalism. The depiction of the concept nationalism varies in terms of culture between both the countries. In Malaysia, the concept of nationalism is depicted through the unity of the three major races while in India nationalism is portrayed among the Indians. Hence, the election campaigns were successful in Malaysia and India through the consensual power between the leaders and the citizens.